Systematic Literature Review on Implementation of Environmentally Sustainable Banking: Motivation, Benefits, and Challenges - Tiwari, Ghanashyam; Sharma, Neeta Dhusia; Roy, Abhisek Saha (The Indonesian Journal of Accounting Research, 2024)
Despite the fact that implementing environmentally friendly banking encompasses several difficulties, the banking industry is now driven to do so globally. Due to the increasing depletion of natural resources and the worsening effects of climate change, the banking sector must undertake a paradigm shift toward sustainable business practices. The study aims to identify the motivational factors for the implementation of environmental sustainability in banking practices. Furthermore, this study intends to examine the barriers the banking industry faces in implementing and integrating environmental sustainability into their operations through a systematic literature review of 45 research articles published in various databases. The used database covers the period of 2015 to 2023.